Chicken manure as a stimulator of the oil hydrocarbons biodegradation:review - Mandryk, Maryia I.; Maksimovich, Alina Yu.; Kaptselava, Valeryia M.; Tsiareshka, Anton G.; Kulik, Arseni V.; Lukyanchuk, Yelena S.; Gribanova, Ekaterina A.; Vasylenko, Svetlana L. (Experimental Biology and Biotechnology, 2025)
Information on the chemical composition of chicken manure and its microbiological characteristics is presented. The main focus is on the use of chicken manure as a stimulator of the biodegradation of oil hydrocarbons (crude oil, diesel fuel, polycyclic aromatic hydrocarbons). Chicken manure is the main waste product of poultry farming, which can be used as a valuable fertiliser, as it contains nitrogen, phosphorus, potassium, iron and various trace elements. The possibility of using chicken manure as a stimulator of oil hydrocarbons biodegradation is due to its content of not only biogenic elements, macro- and microelements necessary for decomposer bacteria, but also the decomposer bacteria themselves, as well as carbon cosubstrates for the degradation of difficult-to-decompose hydrocarbons. For this purpose, chicken manure can be used either independent or in combination with other additives (biocompost, biosurfactants, decomposer bacteria, mineral salts). Applying chicken manure to the soil can lead to an increase in its temperature, which also contributes to more active degradation of oil products. As a result of treating contaminated soils with chicken manure, their toxicity to plants and test objects such as Photobacterium phosphoreum and Paramecium caudatum is reduced.
Keywords: chicken manure; microbiota; decomposer microogranisms; oil hydrocarbons; polycyclic aromatic hydrocarbons; PAH; stimulation of biodegradation; degradation effectiveness